2009 IEEE International Workshop on Machine Learning for Signal Processing 2009
DOI: 10.1109/mlsp.2009.5306220
|View full text |Cite
|
Sign up to set email alerts
|

Exact filtering and smoothing in short or long memory stochastic switching systems

Abstract: Abstract-Let X be a hidden real stochastic chain, R be a discrete finite Markov chain, Y be an observed stochastic chain. In this paper we address the problem of filtering and smoothing in the presence of stochastic switches where the problem is to recover both R and X from Y. In the classical conditionally Gaussian state space models, exact computing with polynomial complexity in the time index is not feasible and different approximations are used. Different alternative models, in which the exact calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Thus different approximations, deterministic [22] or stochastic [3,16,64], have to be used. More recently, it has been shown that considering a TMC T = (X, U, Y ) in which (U, Y ) is Markovian makes both computations feasible with complexity linear in time ( [58] and references therein). Such models can be extended in numerous directions; in particular, copulas could be used in the PMC (U, Y ).…”
Section: Filtering and Smoothing In Switching Linear Systemsmentioning
confidence: 99%
“…Thus different approximations, deterministic [22] or stochastic [3,16,64], have to be used. More recently, it has been shown that considering a TMC T = (X, U, Y ) in which (U, Y ) is Markovian makes both computations feasible with complexity linear in time ( [58] and references therein). Such models can be extended in numerous directions; in particular, copulas could be used in the PMC (U, Y ).…”
Section: Filtering and Smoothing In Switching Linear Systemsmentioning
confidence: 99%
“…Plus récemment il a été proposé différents modèles « à sauts », dont certains très simples, dans lesquels le problème peut être résolu de manière exacte avec une complexité linéaire en n . Leur synthèse est présentée dans (Pieczynski et Abbassi, 2009 ;Abbassi, 2012). Ensuite, un modèle général, appelé « modèle caché conditionnellement linéaire à sauts markoviens » (MCCLSM), unifiant et étendant les différent modèles précédents, a été proposé dans (Pieczynski, 2011a).…”
Section: Introductionunclassified